2007
DOI: 10.1128/jvi.00760-07
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-Cell Markers, Indoleamine 2,3-Dioxygenase, and Virus Levels in Spleen and Gut during Progressive Simian Immunodeficiency Virus Infection

Abstract: High levels of viral replication occur in gut-associated lymphoid tissue (GALT) and other lymphoid tissues (LT) since the early phase of human/simian immunodeficiency virus (HIV/SIV) infection. Regulatory T cells (Treg), a subset of immunosuppressive T cells expressing CTLA-4 and the FoxP3 transcription factor, accumulate in LT during HIV/SIV infection. Here we show that FoxP3 and CTLA-4 mRNA are increased in leukocytes from the spleens, lymph nodes (LN), and mucosal sites of chronically SIV-infected macaques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 50 publications
5
95
1
3
Order By: Relevance
“…It has been shown that SIV/HIV induces increased expression of IDO, an immunosuppressive enzyme that is capable of inducing CD4 Tregs (58). This increase in IDO expression is detected in lymphoid and intestinal mucosal tissues as early as 7 d after SIV infection (30,31,37,59). Similarly, TGF-b has also been shown to induce expression of FOXP3 by mouse naive CD8 + T cells following stimulation with anti-CD3 and anti-CD28 (60).…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown that SIV/HIV induces increased expression of IDO, an immunosuppressive enzyme that is capable of inducing CD4 Tregs (58). This increase in IDO expression is detected in lymphoid and intestinal mucosal tissues as early as 7 d after SIV infection (30,31,37,59). Similarly, TGF-b has also been shown to induce expression of FOXP3 by mouse naive CD8 + T cells following stimulation with anti-CD3 and anti-CD28 (60).…”
Section: Discussionmentioning
confidence: 92%
“…Studies on gene expression in tissue RNA demonstrate a significant increase in the expansion of CTLA-4, IDO, and TGF-␤ in chronically infected macaques (19,23). However, transient expression of these markers by newly activated T cells, not only by T reg , precludes an accurate assessment of the importance of T reg in AIDS pathogenesis using gene expression or phenotypic markers.…”
Section: Cd4mentioning
confidence: 99%
“…Some reports conclude that T reg or T reg -associated markers are decreased in blood of HIV-1-infected individuals while others indicate an increase of T reg in tissues (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Even during the stages of SIV infection, the dynamics of T reg distribution are unclear.…”
Section: Foxp3mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently described the dynamics of adaptive immunity in these macaques 33,46 and showed a transient expansion of CD25 bright CD8 ϩ T cells, which express FoxP-3 and CTLA-4-2 molecules expressed by regulatory T cells (Tregs)-9 to 35 days after infection. 33 Because IDO was recently shown to be induced by HIV in pDCs in vitro 21 and to correlate with viral load in HIV infection, 29 and because pDCs expressing IDO activate Tregs in a mouse tumor model, 47 we searched for the correlation between IDO activity and FoxP3 ϩ CD8 ϩ T-cell subset expansion in vivo. IDO activity correlated not only with plasma viral load (Spearman rank correlation P ϭ .0005, ϭ 0.84) but also with transient expansion of the FoxP3 ϩ CD25 ϩ CD8 ϩ T-cell subset (P ϭ .0005, ϭ 0.85; Figure 6A,B).…”
Section: Org Frommentioning
confidence: 99%